Amygdala functional connectivity in major depression – disentangling markers of pathology, risk and resilience. Issue 16 (22nd December 2020) - Wackerhagen, Carolin; Veer, Ilya M.; Erk, Susanne; Mohnke, Sebastian; Lett, Tristram A.; Wüstenberg, Torsten; Romanczuk-Seiferth, Nina Y.; Schwarz, Kristina; Schweiger, Janina I.; Tost, Heike; Meyer-Lindenberg, Andreas; Heinz, Andreas; et al.
Abstract: Background: Limbic-cortical imbalance is an established model for the neurobiology of major depressive disorder (MDD), but imaging genetics studies have been contradicting regarding potential risk and resilience mechanisms. Here, we re-assessed previously reported limbic-cortical alterations between MDD relatives and controls in combination with a newly acquired sample of MDD patients and controls, to disentangle pathology, risk, and resilience. Methods: We analyzed functional magnetic resonance imaging data and negative affectivity (NA) of MDD patients ( n = 48), unaffected first-degree relatives of MDD patients ( n = 49) and controls ( n = 109) who performed a faces matching task. Brain response and task-dependent amygdala functional connectivity (FC) were compared between groups and assessed for associations with NA. Results: Groups did not differ in task-related brain activation but activation in the superior frontal gyrus (SFG) was inversely correlated with NA in patients and controls. Pathology was associated with task-independent decreases of amygdala FC with regions of the default mode network (DMN) and decreased amygdala FC with the medial frontal gyrus during faces matching, potentially reflecting a task-independent DMN predominance and a limbic-cortical disintegration during faces processing in MDD. Risk was associated with task-independent decreases of amygdala-FC with fronto-parietal regions and reduced faces-associated amygdala-fusiform gyrus FC. Resilience corresponded to task-independent increases in amygdala FC with the perigenual anterior cingulate cortex (pgACC) and increased FC between amygdala, pgACC, and SFG during faces matching. Conclusion: Our results encourage a refinement of the limbic-cortical imbalance model of depression. The validity of proposed risk and resilience markers needs to be tested in prospective studies. Further limitations are discussed.